Breaking the Barriers for Women Participation in Agroforestry in the Context of AfCFTA - Patrick Opoku; Awonlimali Kenneth Ali; Peter Ampadu-Daaduam; Dorothy Asare Akoto (African Journal on Land Policy and Geospatial Sciences)
Agroforestry, an integrated land management practice combining agriculture, forestry, and natural resource conservation, holds significant potential for sustainable development and economic growth in Africa. With the establishment of the African Continental Free Trade Area (AfCFTA), there arises a unique opportunity to leverage agroforestry for food security, environmental protection, and poverty alleviation. However, women's participation in agroforestry remains limited, obstructing the realization of its full potential. The goal and objectives of the study are; (a) to assess the factors that derive women participation in agroforestry, (b) to analyze the challenges women, face with agroforestry practices, and (d) to identify ways of improving women participation in agroforestry. The study used a case study research design with data from both primary and secondary sources. Primary data was gathered through questionnaire administered to a sample of 100 respondents in Sefwi Wiawso municipality in Ghana. Exploratory factor analysis involving principal component analysis was used for the data analysis. The study found out that Taungya farming, home garden, and forest farming were the types of agroforestry systems carried out by women in the study area. Findings showed that women participate in agroforestry mainly for income, job, environmental protection, food security and boundary protection reasons. Challenges they face include lack of access to land, credits, markets and capital. Equal resource access, training, and market opportunities are essential for enhancing women's involvement in agroforestry, promoting gender equality, and sustainable agroforestry systems.